Keratoconus with two consecutive re-emergences: a case report - Peicheng Zhang; Yanchao Wu; Lixiao Ma; Dong Wang (BMC Ophthalmology)
Abstract Background Keratoconus is a common disease in clinical practice, and deep anterior lamellar keratoplasty(DALK) is a conventional treatment for keratoconus, which is effective and not easy to recur after surgery. Case presentation The author presents a rare case report involving a 21-year-old patient with Consecutive re-emergences of Keratoconus. He underwent DALK for keratoconus in his left eye in 2012 and experienced re-emergence 3 years later, followed by a second deep lamellar keratoplasty in the same year. In 2019, the patient experienced re-emergence of keratoconus and underwent a third deep lamellar keratoplasty in the same eye. Genetic testing was performed, and no abnormal genes were identified. Postoperative follow-up emphasized the management of chronic allergic conjunctivitis (CAC) and the correction of eye-rubbing habits. To date, he has not experienced any further re-emergence. Conclusions Keratoconus is a complex disorder with a multifaceted etiology and pathogenesis, including genetic, environmental, biomechanical, and cellular factors. Its treatment usually requires multiple considerations, including the choice of surgical methods, anti-inflammatory therapy, and correction of eye rubbing habits to guide patients for subsequent treatment interventions.